Mathematical programming and simulation based layout planning of container terminals. (10th April 2010) - Wiese, Jorg; Suhl, Leena; Kliewer, Natalia
Container terminal operators are under pressure to handle the increasing amount of container transfer in the global transportation network. To manage the growth, new container terminals are built or the capacity of existing ones is expanded using modern container handling technologies as well as automatic equipment. An efficient layout of the container terminal is crucial to obtain the maximum capacity. In this paper we present an approach based on a mixed integer linear model to find promising layout configurations for container terminals. Means of simulation are used to validate and evaluate the attained layout configuration. In addition the adequacy of the mixed integer linear model for planning layouts of container terminals is evaluated using the developed simulation model.